2018
DOI: 10.1590/0034-7167-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Social Representations of health care professionals on Acquired Immune Deficiency Syndrome

Abstract: The findings show that, despite the advances in the health area regarding the treatment of AIDS, prejudice still persists. It is important to strengthen interdisciplinary actions focused on discussions on this theme during training, favoring the comprehensiveness of the assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…However, a descriptive study carried out in Bahia, Brazil, involving professionals from health and social sciences who worked directly with people living with HIV/AIDS demonstrated that despite the advances related to the approach and management in the treatment of this disease, the prejudice among these professionals still persists and can negatively influence their practice of care provision. Thus, it is necessary to strengthen interdisciplinary actions in order to promote comprehensive care, free from any stereotype, with a view to promoting the quality of life of people living with HIV/AIDS (18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a descriptive study carried out in Bahia, Brazil, involving professionals from health and social sciences who worked directly with people living with HIV/AIDS demonstrated that despite the advances related to the approach and management in the treatment of this disease, the prejudice among these professionals still persists and can negatively influence their practice of care provision. Thus, it is necessary to strengthen interdisciplinary actions in order to promote comprehensive care, free from any stereotype, with a view to promoting the quality of life of people living with HIV/AIDS (18) .…”
Section: Discussionmentioning
confidence: 99%
“…In the social dimension, the detachment from friends and family stands out, hindering family interactions, making individuals to isolate in society and have low self-esteem (4) . The feeling of guilt can also occur when a condition is considered a social deviation from the heteronormative idea that still prevails in the current collective imagination (18) .…”
Section: Discussionmentioning
confidence: 99%
“…La historia brasileña y mundial de la epidemia causada por el virus de la inmunodeficiencia humana (VIH) está marcada por profundas transformaciones epidemiológicas, sociales y políticas (1,2) . Esas transformaciones son percibidas desde las formas de presentación de conceptos e imágenes hasta las actitudes frente al virus, lo que lo convirtió en un fenómeno social sensible y, por lo tanto, sujeto a representaciones sociales (3,4) .…”
Section: Introductionunclassified
“…Além do preconceito por parte da população geral, como é visto por esses participantes, um estudo realizado com profissionais da saúde de serviços especializados em HIV mostrou que, apesar dos avanços na área de saúde, ainda existe preconceito entre os profissionais que são responsáveis pelo cuidado desses pacientes, sugerindo a necessidade de fortalecer ações que promovam a discussão entre a equipe com o objetivo de romper esses estereótipos (Suto et al, 2018).…”
Section: Motivos Relacionados Ao Baixo Peso Atualmenteunclassified